The importance of pre-training gap analyses and the identification of competencies and skill requirements of medical personnel for mass casualty incidents and disaster training - Goniewicz, Krzysztof; Goniewicz, Mariusz; Włoszczak-Szubzda, Anna; Burkle, Frederick M.; Hertelendy, Attila J.; Al-Wathinani, Ahmed; Molloy, Michael Sean; Khorram-Manesh, Amir (BMC public health, 2021)
Background Effective preparedness to respond to mass casualty incidents and disasters requires a well-planned and integrated effort by all involved professionals, particularly those who are working in healthcare, who are equipped with unique knowledge and skills for emergencies. This study aims to investigate and evaluate the level of knowledge and skills related to mass casualty and disaster management in a cohort of healthcare professionals. Methods A cross-sectional brief study was conducted using a validated and anonymous questionnaire, with a sample of 134 employees at a clinical hospital in Lublin, Poland. Results The findings of this study may indicate a need for standardization of training for hospitals employees. It also suggests a knowledge gap between different professional groups, which calls for adjusting such general training, to at least, the weakest group, while special tasks and mission can be given to other groups within the training occasion. Conclusion Pre-Training gap analyses and identification of participants’ competencies and skills should be conducted prior to training in mass casualty incidents and disasters. Such analyses provides an opportunity to develop training curriculum at various skill and knowledge levels from basic to advance. All training in mass casualty incidents and disasters should be subject to ongoing, not just periodic, evaluation, in order to assess continued competency.